Measuring the water content in freshly-deposited fingermarks. (January 2019) - Keisar, Or; Cohen, Yair; Finkelstein, Yacov; Kostirya, Natalie; Ben-David, Roey; Danon, Albert; Porat, Ze'ev; Almog, Joseph
Highlights: The water content of freshly deposited fingermarks has been measured. A wide range of water concentrations — generally between 20 and 70% has been found. The commonly accepted water content — 98–99% was not encountered. Abstract: The literature view regarding the composition of deposited fingermarks has long been that the average water content is in the range of 98–99 wt.%. This value has recently been challenged by Kent, claiming that it should be 20 wt.% at most. Herein we have measured the weight percentage of water content in freshly-deposited fingermarks, with and without hand pre-washing. Two complementary techniques were utilized for the measurements, namely quartz crystal microbalance (QCM) for determining the relative mass-loss and its rate at ca. 37 °C, and temperature-programmed desorption-mass spectrometry (TPD-MS) for establishing that the mass loss arises solely from the complete evaporation of all the water content in the fingermarks (done with hand pre-washing only). Unlike the traditional narrow-range values of 98–99% and the limiting value of 20 wt.% suggested by Kent, our measurements indicate the occurrence of a broad 20–70% water content. Higher contents of water in fingermarks were found post hand pre-washing, most probably due to removal of the sebum from the fingertips, but none of the results exceeded 90%.